Communications Between Bone Marrow Macrophages and Bone Cells in Bone Remodeling - Chen, Kaixuan; Jiao, Yurui; Liu, Ling; Huang, Mei; He, Chen; He, Wenzhen; Hou, Jing; Yang, Mi; Luo, Xianghang; Li, Changjun (Frontiers in Cell and Developmental Biology, 2020)
The mammalian skeleton is a metabolically active organ that continuously undergoes bone remodeling, a process of tightly coupled bone resorption and formation throughout life. Recent studies have expanded our knowledge about the interactions between cells within bone marrow in bone remodeling. Macrophages resident in bone (BMMs) can regulate bone metabolism via secreting numbers of cytokines and exosomes. This review summarizes the current understanding of factors, exosomes and hormones that involved in the communications between BMMs and other bone cells including mensenchymal stem cells, osteoblasts, osteocytes and so on. We also discuss the role of BMMs and potential therapeutic approaches targeting BMMs in bone remodeling related diseases such as osteoporosis, osteoarthritis, rheumatoid arthritis and osteosarcoma.